Unilateral Climate Policy: Can OPEC resolve the Leakage Probem? - Christoph Böhringer; Knut Einar Rosendahl; Jan Schneider (University of Oldenburg, Department of Economics, 2013)
In the abscence of a global agreement to reduce greenhouse gas emissions, individual countries have introduced national climate policies. Unilateral action involves the risk of relocating emissions to regions without climate regulations, i.e., emission leakage. A major channel for leakage are price changes in the international oil market. Previous studies on leakage have assumed competitive behaviour in this market. Here, we consider alternative assumptions about OPEC's behaviour in order to assess how these affect leakage and costs of unilateral climate policies. Our results based on simulations with a large-scale computable general equilibrium model of the global economy suggest that assumptions on OPEC's behaviour are crucial to the impact assessment of unilateral climate policy measures. We find that leakage through the oil market may become negative when OPEC is perceived as a dominant producer, thereby reducing overall leakage drastically compared to a setting where the oil market is perceived competitive.
Keywords: C72; Q41; Q54; 330; Carbon Leakage; Oil Market; OPEC Behaviour; Klimaschutz; Ölpreis; Kartell; Treibhausgas-Emissionen; Auslandsverlagerung; Allgemeines Gleichgewicht; Welt; OPEC-Staaten